PROFIL KONDISI STRES DI MASA PANDEMI COVID-19 SEBAGAI DASAR INTERVENSI DALAM PRAKTEK MIKROKONSELING - Sudharno Dwi Yuwono (Universitas Muhammadiyah Tapanuli Selatan, 2020)
There is no one who can confirm when pandemic will be end. Many informations, infodemic, lead someone to have anxiety. In addition, there are changes in real life activities to be more frequent into cyberspace activities. These three things become strong stressor for the people during the COVID-19 pandemic. This study aims to obtain a profile of citizen conditions during the pandemic that can be used in micro counseling practices. The research used survey methods specifically using Perceived Stress Scale instrument (PSS 10). This study had 127 respondents that selected by using convenience sampling technique. Based on the research, the stress condition of the respondents are 65% in the medium category, 30% in the low category and 5% in the high category.